A Post Keynesian Explanation of the Causes of the Current World Slupm - Jan Kregel (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
This paper argues that the current global recession may be enterpreted as the widely anticipated post-war continuation of the Great Depression some 40 years later. It suggests that those factors which prevented the resumption of slump conditions was the inability of the Bretton Woods conference to find a suitable solution to the problem of asymmetric adjustment of debtor and creditor countrie. Once the US became a mejor debtor country this lacuna created difficulties which eventually eliminated those factors responsible for the post-war recovery.
Keywords: 330